ANALYSIS OF ISLAMIC EDUCATION IN THE ERA OF KHULAFA AR-RASHIDIN AND ABBASID DINASTY - Lahmi, Ahmad; Ermawita, Yulia (JURNAL ISLAMIKA, 2022)
This study aims and analyze the education of the Khulafa ar-Rashidin and Abbasid eras. The method of this type of research is library research, where the researcher tries to collect data that has a relationship with the theme being discussed. The data is obtained from various documents such as; books, papers, journals, and articles related to education in the era of the khulafa ar-Rashidin and the Abbasids. Then, the researcher is the research instrument itself where the work of determining research, selecting data sources, collecting data, assessing data quality, analyzing data, elaborating, and the conclusions of the findings are carried out by the researcher. The collected data were analyzed critically and synthesized which then presented the results of the study that answered the objectives of this research. Then, the results of this study found three main things, namely: first, educational materials in the era of Khulafa ar-Rashidin included reading and writing, grammar, hadith, sya'ir, nahwu, sharaf, basic mathematics, stories, swimming, archery, and riding, memorizing Qur'an and examines the basics of Islam, namely monotheism education, prayer, etiquette in the family and society, personality and defense, and security. This material is given in general because there is no educational level. Meanwhile, in the Abbasid era, educational materials included compulsory and optional subjects. Compulsory lessons such as the Qur'an, prayer, nahwu, sharaf, Arabic, and reading and writing. Optional materials such as arithmetic, nahwu, sharaf, Arabic, poetry, and history of the Arabic. Second, the educational methods of the Khulafa ar-Rashidin era were lectures, memorization, exercises, and discussions. While the methods of Islamic education in the Abbasid era were oral, written, memorization, discussion, and discovery or research methods. Third, the education system of the Khulafa ar-Rashidin era, namely the halaqah and Abbasid systems, namely the halaqah and classical systems or formal and non-formal systems.